KARAKTERISASI MINUMAN HERBAL CELUP DENGAN PERLAKUAN KOMPOSISI JAHE MERAH : KUNYIT PUTIH, DAN JAHE MERAH : TEMULAWAK - Adi Listiana; Herlina - (UNIVED Press, Universitas Dehasen Bengkulu, 2015)
This study aimed to obtain the characteristics of ginger herbal drink red dye : white saffron and red ginger : ‘temulawak”. This study consisted of two phases. The first stage aims to determine the antioxidant activity in treatment variations of red ginger: white turmeric and red ginger : “temulawak”. The second phase aims to determine the level of consumer preferences to drink herbal teabag research results . The results showed that the antioxidant activity of treatment variations of red ginger and turmeric highest white with treatment variations 1.5 : 0.5 g , amounting to 83.98 % RSA , while the lowest value in the treatment of variation 1.0 : 1.0 g with 82.87 % RSA results . The antioxidant activity in red ginger and turmeric treatment ranged from 86.34 % until 87.22 % RSA , while the preference level panelists to colors ranging from 3.60 ( like ) until 3.95 ( like) , aroma 3:40 ( rather like ) until 4.00 ( like ) and the flavor was not significant.Keyword : red ginger, white turmeric, “temulawak”, antioxidant activity